Minat Mahasiswa Terhadap Mata Kuliah Kewirausahaan - Hamdani Hamdani (Politeknik Kutaraja, 2021)
Based on reports from the Aceh Central Statistics Agency (BPS), open unemployment is dominated by college graduates. The results showed that the application of an effective entrepreneurship curriculum can foster student interest in entrepreneurial activities. This is indicated by the evidence that 57 percent of students taking entrepreneurship courses in this study have opened a business since college and 21.8 percent will start a business less than 1 year after graduating from college. This research was conducted in May-June 2020 with the method of statistical descriptive and analysis crosstabs. The population is the Kutaraja Banda Aceh Polytechnic students and a sample of all study program students who have taken entrepreneurship courses. This study confirms previous research that found entrepreneurship curriculum to be effective in reducing college graduate unemployment.